Design Manufacture of Fixture Fire Fighter Kit - Wirda Novarika; Fatahul Arifin; Eka Satria Martomi; Indra Gunawan; Fathur Raihan Perdana (Yayasan Ghalih Pelopor Pendidikan (Ghalih Foundation), 2021)
Forest fires are one that needs attention in Indonesia. Due to spent a lot of money to solve this problem. One of the tools to solve this problem is fire fighter, so in case is need to make the fixture can manufacture the fire fighter kit. In this study, we propose the fixture that can be produce the kit. It call fixture fire fighter kit. Autodesk inventor is applied in the simulation design and also it is considering with the ergonomic for the worker especially the Indonesian male. Finally, this tool can be resistant with load 50 kg, the deflection is 0.831 mm, and the maximum von misses stress is 34.12 MPa.